The impacts of network competence, knowledge sharing on service innovation performance: Moderating role of relationship quality - Zaoquan Jian; Chen Wang (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: To examine how network competence, knowledge sharing and relationship quality affect service innovation performance Design/methodology/approach: Empirical Research Findings: 1) Both enterprise's network competence and knowledge sharing have distinct positive impact on SIP; (2) Knowledge sharing partially mediates the effect of network competence on SIP. (3) Relationship quality positively moderates the effect of network competence on knowledge sharing, and the effect of knowledge sharing on SIP. (4) Relationship quality does not positively moderate the effect of network competence on SIP. Originality/value: This study has enriched current understanding of the relationship among network competence, knowledge sharing, relationship quality and service innovation performance.
Keywords: 650; Service Innovation Performance (SIP); Network Competence (NC); Relationship Quality (RQ); Knowledge Sharing (KS)